STRATEGI BAZNAS KOTA PADANG DALAM MEMBERDAYAKAN MASYARAKAT MISKIN MELALUI JAMA’AH MASJID - Yuliasni, Yuliasni (JURNAL AL-IJTIMAIYYAH, 2020)
Community empowerment efforts by the City of Baznas in Padang are through a program created as a form of productive zakat utilization and the distribution carried out by BAZ must be prioritized for productive and well-targeted businesses. From this description, the researcher formulated the problem in three research problem formulations, namely 1. How is the Baznas strategy of Padang City in empowering the poor with the requirements of mosque/mushalla worshipers. 2. How is the implementation of empowering the poor by the Padang City Baznas on the condition of being a mosque/mushalla congregation? And 3. What are the inhibiting and supporting factors of Padang City Baznas in empowering the poor on the condition of being a mosque/mushalla congregation? This research is a field research (field research) using descriptive qualitative method. The results of this study are the Baznas Padang City strategy in empowering the poor with the requirements of the mosque/mushalla congregation, which was conducted in 2011. Then it will not be discussed in the Padang City Baznas. Implementation of empowerment of the poor by the Padang City Baznas on the condition of being a congregation mosque, in the field there was found a mosque or mushalla that provided convenience, however there were also mosque or mushalla administrators who were indeed selective in providing the request letter, because they were contacted with the surrounding public assistance . The inhibiting factor of the City of Padang Baznas in empowering the poor on the condition of being a mosque/mushalla congregation is the lack of understanding of the community towards the purpose of the inclusion of the congregational active statement. While the supporting factors are the City of Padang Baznas has strength, support and support from the government, has experienced human resources, and has a strategic location on the edge of the By Pass road in the city of Padang.Keywords: Strategy, Baznas, Empowering, The Poor, and Jama'ah Mosque.